Basic Substances in Organic Agriculture: Current Status - Orconneau, Yann; Taylor, Alex; Marchand, Patrice A. (Chronicle of Bioresource Management, 2023)
Basic substances are one of the new categories of active substances created under the “new” plant protection products (PPP) Regulation EC 1107/2009. They are approved for use in the European Union and are mostly biorationals, medicinal plant extracts, products used in human medicine, food compounds or additive and common substances sold as biocide, fertiliser or cosmetic but now triggered to be used as plant protection means. A list of 24 basic substances approved is available through the EU Pesticides database. However, numerous applications of biorationals as basic substances were rejected, from inadmissibility or ineligibility, through abandonment or withdrawal, to non-approval, with the explanation for these decisions, their excessive risk for the operators, applicators or consumers by the substance itself or its possible residues. Nevertheless, these substances are still sold for their original purpose, without any modification which would have been expected due to this risk evaluation conclusions. In sum, it is too dangerous to use them in crop protection.